Calidris maritima (Charadriidae) - Nahrungserwerb - Rüppell, Georg (IWF (Göttingen), 1968)
Der Meerstrandläufer ernährt sich omnivor. Mit seinem Schnabel stochert er im Schlickboden und in Wasserlachen nach Nahrung; Putzen. : The film shows the purple sandpiper searching for food. Several birds are poking about for nourishment in the sand and mud near the waterline.